Inhibited intracrystalline cracks and enhanced electrochemical properties of NCM811 cathode materials coated by EPS. Issue 23 (1st December 2021) - Tan, Xinru; Zhang, Maolin; Zhang, Dongyan; Yan, Yangxi; Wang, Yuan; Li, Zhimin
Abstract: The formation of micro-cracks in Ni-rich LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) cathode particles is an extremely important factor affecting the electrochemical characteristics after long-term cycling. Generally, cracks can be divided into intergranular crack and intracrystalline crack according to their positions. Coating has been confirmed as a highly effective strategy to relieve intergranular cracks. However, the intracrystalline cracks of primary-like particles have rarely been studied. In this work, ethoxy functional polysiloxane (EPS) was directly coated on the surface of original NCM811 by tetraethyl orthosilicate (TEOS) hydrolytic polycondensation method without any additives. Then, the microstructure, micromorphology, surface state and electrochemical properties were investigated in detail by XRD, SEM, TEM, CV and EIS. The results displayed that the micro-cracks of primary-like particles were effectively suppressed under appropriate EPS coating. Accordingly, excellent capacity retention of 95.6% (100 cycles, 1C) and rate performance (144.6 mA h/g, 5C) were obtained. These improved mechanical and electrochemical properties are considered to be related to the EPS stress buffer layer, suppressed oxygen vacancies, inhibited phase transition and reduced volume change.